Pendampingan Digitalisasi Pembukuan Keuangan Menggunakan Aplikasi Android Siapik Pada Umkm Bumbu Instan Lazizaf di Jakarta Timur - Rizqi, Az Zahroh; Virandadipa, Dwika; Rahmadi, Zara Tania; Yulianto, Kampono Imam; Setiawan, Indra; Dharma, Dias Adhi; Wahyudi, Muhammad Aria (ASOSIASI IDEBAHASA KEPRI, 2024)
This research aims to analyze the socialization process and provide assistance in making simple financial bookkeeping reports for micro, small and medium enterprises (MSMEs) in Matraman, East Jakarta. The method used is a case study with a qualitative approach. Data was collected through in-depth interviews with MSME owners and financial managers as well as direct observation of the practices carried out in preparing financial reports. The research results show that intensive socialization and the practice of making simple financial reports provide significant benefits for MSMEs in developing their financial understanding and skills.